Improving Numeracy Performance Through the GASING Method - Rita Yuana; Iip Saripah; Zia Zalzilah Mazfufah; Yohanes Surya; Yanti Shantini; Dadang Yunus Luthfiansyach; Ethel Joy V. Sebastian (Hipotenusa: Journal of Mathematical Society, 2026)
Numeracy is foundational to academic success, yet many Indonesian primary school students struggle with mathematics under instruction that emphasises rote memorisation over conceptual understanding. This study examined the improvement in numeracy performance associated with the GASING (Gampang, Asyik, Menyenangkan / Easy, Enjoyable, Fun) method among primary school students and teachers in Bojonegoro District, Indonesia. A one-group pre-test–post-test design was employed with 97 students and 50 teachers who completed a 15-day intensive training programme covering five numeracy domains: number recognition, addition, multiplication, subtraction, and division. Performance was assessed using curriculum-aligned numeracy tests administered at pre-test and post-test. Paired-samples t-tests showed statistically significant gains across all domains. Students improved from a composite pre-test mean of 30.51 (SD = 17.55) to 83.08 (SD = 9.53), t(96) = 35.25, p < .001, Cohen's dz = 3.58, equivalent to a 2.72-fold gain; the largest domain gain was in division (6.28-fold). Teachers improved from 73.56 (SD = 13.11) to 97.70 (SD = 2.98), t(49) = 15.16, p < .001, dz = 2.14. Because the design included no control group, these results indicate improvement associated with the intervention rather than its isolated causal effect. The findings nonetheless suggest that the GASING method, delivered through an integrated teacher–student training model, is associated with substantial numeracy gains and with positive affective changes reported by participants.